Undersizing of aged African biomass burning aerosol by an ultra-high-sensitivity aerosol spectrometer - S. G. Howell (Copernicus Publications, 2021)
The ultra-high-sensitivity aerosol spectrometer (UHSAS) differs from most other optical particle spectrometers by using a high-power infrared (IR) laser to detect small particles and reduce the sizing ambiguity due to the non-monotonicity of scattering with particle size.